2019
DOI: 10.1111/bph.14875
|View full text |Cite
|
Sign up to set email alerts
|

A bivalent antihypertensive vaccine targeting L‐type calcium channels and angiotensin AT1 receptors

Abstract: Background and Purpose: Hypertension has been the leading preventable cause of premature death worldwide. The aim of this study was to design a more efficient vaccine against novel targets for the treatment of hypertension.Experimental Approach: The epitope CE12, derived from the human L-type calcium channel (Ca V 1.2), was designed and conjugated with Qβ bacteriophage viruslike particles to test the efficacy in hypertensive animals. Further, the hepatitis B core antigen (HBcAg)-CE12-CQ10 vaccine, a bivalent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
10
0
2
Order By: Relevance
“…An alternative approach could target AT1R (AT1R-B2R), and the L-type calcium channel simultaneously [135]. The experimental strategy uses a bivalent vaccine against the AT1 receptor and the L-type calcium channel, and thereby simultaneously inhibits the AT1 receptor and the Cav 1.2 channels as the major L-type calcium channel in humans [135].…”
Section: Inhibition Of Exaggerated At1r-b2r-stimulated Calcium Signaling Of Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach could target AT1R (AT1R-B2R), and the L-type calcium channel simultaneously [135]. The experimental strategy uses a bivalent vaccine against the AT1 receptor and the L-type calcium channel, and thereby simultaneously inhibits the AT1 receptor and the Cav 1.2 channels as the major L-type calcium channel in humans [135].…”
Section: Inhibition Of Exaggerated At1r-b2r-stimulated Calcium Signaling Of Preeclampsiamentioning
confidence: 99%
“…An alternative approach could target AT1R (AT1R-B2R), and the L-type calcium channel simultaneously [135]. The experimental strategy uses a bivalent vaccine against the AT1 receptor and the L-type calcium channel, and thereby simultaneously inhibits the AT1 receptor and the Cav 1.2 channels as the major L-type calcium channel in humans [135]. The bivalent vaccine effectively lowered blood pressure and prevented end-organ damage in experimental models of hypertension in mice and rats, without major side effects [135].…”
Section: Inhibition Of Exaggerated At1r-b2r-stimulated Calcium Signaling Of Preeclampsiamentioning
confidence: 99%
“…Wu et al reported the development of vaccines with VLPs against the L-type calcium channel for the treatment of hypertension in SHRs [ 36 ]. A peptide (named CE12) was derived from the epitope of the third extracellular region of domain IV of the human L-type calcium channel [ 37 , 38 ], and after four injections, systolic BP was significantly decreased in vaccinated SHRs compared with unvaccinated rats.…”
Section: Therapeutic Vaccines For Hypertensionmentioning
confidence: 99%
“…Wu et al reported the development of vaccines against the L-type calcium channel for treatment of hypertension in SHRs. 42 The peptide (named CE12) was derived from the epitope of the third extracellular region of domain IV of the human L-type calcium channel, which plays an important role in allosteric modulation after binding to 1,4-dihydropyridines. 43,44 They used a VLP as a carrier protein.…”
Section: Calcium Channelmentioning
confidence: 99%